Moving Together, Learning Together: Developing Cooperation Skills Through the Flag Relay Game - Muthiah Amalia Humairoh; Dodi Harianto; Sapriya Utami (JOYCED: Journal of Early Childhood Education, 2026)
Purpose – Cooperation skills are essential for children’s social-emotional development. However, observations at Al-Falah Islamic Kindergarten, Jambi City, indicated that children aged 5–6 years demonstrated low levels of cooperation, including limited teamwork, sharing behavior, and compliance with group rules. Although play-based learning has been widely applied in early childhood education, limited studies have examined the effectiveness of flag relay games in improving cooperation skills. Based on sociocultural learning theory, this study aimed to determine the effectiveness of flag relay games in improving children’s cooperation skills. Design/methods/approach – This Classroom Action Research (CAR) involved 11 children in Group B of Al-Falah Islamic Kindergarten, Jambi City. The study was conducted in two cycles consisting of planning, action, observation, and reflection stages. Data were collected through observations, interviews, and documentation and analyzed using descriptive quantitative and qualitative techniques. Findings – The results showed a significant improvement in children’s cooperation skills following the implementation of the flag relay game. Classical completeness increased from 36.36% in the pre-cycle stage to 63.64% in Cycle I and reached 90.91% in Cycle II, exceeding the predetermined success criterion of ≥76%. Research implications/limitations – The study was limited to a small number of participants in one kindergarten setting. Nevertheless, the findings suggest that flag relay games can effectively promote cooperation skills and social interaction among young children. Originality/value – This study highlights the use of flag relay games as an interactive and collaborative learning strategy to enhance cooperation skills in early childhood education.